Creating Economic Growth Lessons for Europe - Magnani, M. (Palgrave Advances in Regional and Urban Economics, 2014)
As national leaders struggle to revive their economies, the people of Europe face a stark reality, which has created an opportunity for local leaders and citizen movers and shakers to rise to the occasion to spur revitalization from the bottom up. The author offers a six-point plan to prosperity.